A study on otitis media with special emphasis on acute suppurative otitis media - Moupachi, Surendra Singh; Gupta, Richa; Agrawal, Vishnu; Gupta, Shikha (International Journal of Research in Medical Sciences, 2017)
Background: Otitis media is a common condition in developing countries and requires support and cooperation of both medical professionals and patients for the proper and timely management of this problem. Aim of current study was to present 148 OM (otitis media) cases observed at the S.S. medical college & G.M. hospital, Rewa. Methods:The present study was done on 148 patients of OM (otitis media) who presented to the S.S. Medical College & G.M. Hospital, Rewa prospectively from December 2012 to February 2013. Results:Most patients (56) belong to 11-20 year age group with age ranging from 4 years to 70 years. Male predominance (85) was observed. About 96 patients were from rural areas. Left laterality (60 cases) was commonest. Unsafe CSOM (62 cases) was the commonest type of otitis media seen. ASOM was seen in 20.27% cases. Conclusion:Otitis media is present in this region of country in abundance and need of hour is to spread awareness about the disease.